Francis L. Galt papers - Galt, Francis L., 1831 or 1832-1915.
Journal, letter, and writings documenting Galt's service as a surgeon aboard the Peruvian naval vessel Tambo on an expedition under the command of another Confederate expatriate, John Randolph Tucker, to explore the Amazon River. Includes notes on the health, diet, diseases, and medical practices of the indigenous people of the Amazon region. Also includes an account of the orphan children of Confederate expatriate William Henry Dowd after his death in Peru. Other topics include Peruvian politics and Galt's service aboard the Confederate screw sloop Alabama. Includes typewritten transcripts of Galt's journal and most of his writings.
Typewritten transcript of Galt's journal and most of his writings is available.
Physician and naval surgeon.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Dowd, William Henry, -- 1836-1873.; Tucker, John Randolph; Confederate States of America. -- Navy -- Surgeons; Peru. -- Marina; Alabama (Screw sloop); Tambo (Ship); American Confederate voluntary exiles -- Peru; Indians of South America -- Amazon River Region; Indians of South America -- Amazon River Region -- Diseases; Indians of South America -- Amazon River Region -- Health and hygiene; Indians of South America -- Amazon River Region -- Medicine; Indians of South America -- Amazon River Region -- Nutrition; Amazon River -- Discovery and exploration; Peru -- Politics and government -- 1829-1919.; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil War, 1861-1865 -- Naval operations, Confederate; Naval officers; Physicians